2018
DOI: 10.1002/adv.22142
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of initiator content in the polymerization reaction of a thermoplastic liquid resin for advanced composite manufacturing

Abstract: Considerable interest has been generated in the last years in the use of thermoplastics polymers as matrices in advanced composites manufacturing. In this research, a new Elium® acrylic matrix developed by Arkema has been studied to evaluate the influence of different benzoyl peroxide initiator (Luperox®78) contents on the polymerization reactions for Elium®150. For that, thermal and rheological analyses were performed providing a better understanding of these reactions. The results show that the initiator con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Following an opposite trend, the photoinitiator concentration has also a great influence on the time needed for the polymerization process. A small concentration of TPO means less reactive species in the solution, responsible for slower initiation and propagation rates [ 40 ], so the time for achieving the gel point is higher, and vice versa. Specifically, the effect of increasing the TPO content from 4 up to 10 wt% reduced the gel point time 0.47-fold, 0.54-fold and 0.67-fold for PANI loadings of 2, 3.5 and 5 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following an opposite trend, the photoinitiator concentration has also a great influence on the time needed for the polymerization process. A small concentration of TPO means less reactive species in the solution, responsible for slower initiation and propagation rates [ 40 ], so the time for achieving the gel point is higher, and vice versa. Specifically, the effect of increasing the TPO content from 4 up to 10 wt% reduced the gel point time 0.47-fold, 0.54-fold and 0.67-fold for PANI loadings of 2, 3.5 and 5 wt%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as can be observed in Figure 1 C, the biggest reduction in the gel point time was found after changing the TPO concentration from 6 to 7 wt% for a given PANI content, whereas a further increase in the photoinitiator content did not provide a clear benefit in terms of curing time (the gel point times for T7P5 and T10P5 were similar, within experimental error). As stated by previous authors, when a critical concentration of photoinitiator is exceeded, competitive chain propagation and/or gel effects, associated with the higher concentration of free radicals, delay the reaction propagation and the gel point [ 40 ]. Simultaneously, the effect of crosslinking may be reduced as a result of limited penetration into the material because of rapid crosslinking of the surface layer; therefore, limited polymer crosslinking degree is achieved [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel reactively polymerized liquid thermoplastic resin opens new possibilities for room temperature manufacturing processes such as Vacuum Assisted Resin Infusion (VARI ) [3,4] and Vacuum Assisted Resin Transfer Moulding (VARTM ) [5][6][7]. The acrylic resin undergoes radical polymerization by peroxide compounds initiation resulting in a PMMA like matrix [8]. During the curing step, covalent bonds are created to obtain entangled macromolecular chains with strong interactions between methacrylate side groups and primary carbon of the main chain.…”
Section: Introductionmentioning
confidence: 99%
“…In the thermoplastic composite, it can be observed that the increase in moisture causes an increase in the tanδ curve due to the heterogeneity of the structure. This is due to the increase in the free volume between the monomer units, which in turn affects the polymerization reaction as well as the molecular and diffusion motions . As Elium resin is made up of block copolymers, the water absorption can promote a phase separation giving rise to a new peak and separation of the Tg, in this case, this phenomenon can be observed before the principal peak in Fig.…”
Section: Resultsmentioning
confidence: 99%